Master Students’ Research Culture Development in Pedagogical Education - Mizimbayeva, Almira; Mankesh, Aksaule; Survutaitė, Dalia (Pedagogika, 2015)
One of the principles of the Bologna process is lifelong education, which means that a person should not be able just to gain knowledge for life, studying at the walls of his alma mater, but to master the competencies of self-education and research which enables him to be in a constant process of self-instruction. This is closely linked to the requirements to the Master in Education: who must be able to obtain information, to be able to analyze it, draw conclusions, put properly theory into practice, be able to see the contradictions, to pose problems, be able to seek the best ways and offer effective solutions (Всемирная хартия университетов (1988), Государственный общеобразовательный стандарт образования Республики Казахстан, 2009)). For the successful implementation of the lifelong learning principle and meeting Master of Education training requirements master student’s research culture should be developed. Having acquired the main basis of research culture, students will be able to use it to solve the problems of self-education, thereby self-perfecting throughout their lives. The background, definition and conditions of the master students’ research culture development are discussed in the given article.